Ruminating on the nature of intelligence: Personality predicts implicit theories and educational persistence. (15th July 2017) - Satchell, Liam; Hoskins, Sherria; Corr, Philip; Moore, Roger
Abstract: Research in schools has shown that those who hold Incremental Theories of Intelligence (i.e. intelligence can grow and improve) generally outperform those who hold Entity Theories of Intelligence (i.e. intelligence is 'fixed' and cannot improve). Recently, there have been attempts to establish a stronger theoretical explanation for individual differences in educational success, by relating the Big Five's Conscientiousness to higher school attainment. In this study, we aimed to demonstrate further relationships between Implicit Theories of Intelligence and a well-known neurologically based theory of personality, namely Reinforcement Sensitivity Theory (RST). A sample of 319 adults completed personality measures of RST, the Big Five and Implicit Theories of Intelligence, as well as a proxy measure for educational persistence (highest academic qualification achieved). The results showed that participants who hold an Incremental (growth) Theory of Intelligence score higher on the RST Behavioural Approach System traits oriented toward future reward and the Big Five's Conscientiousness. Those that hold an Entity (fixed) Theory of Intelligence score higher on RST Behavioural Inhibition System and the Big Five Neuroticism measure. The paper discusses the implications of these relationships and explores the benefits of the simultaneous use of both theoretically underpinned and applied measures of individual differences. Highlights: Implicit Theories of Intelligence (ITI) are related to RST personality traits. ITI relate to the commonly used predictor of academic success, Conscientiousness. RST persistence and reward interest traits correlate with academic persistence.